2020
DOI: 10.1002/aocs.12332
|View full text |Cite
|
Sign up to set email alerts
|

“Arbequina” Olive Oil Composition Is Affected by the Application of Regulated Deficit Irrigation during Pit Hardening Stage

Abstract: Three new regulated deficit irrigation (RDI) treatments were applied to "Arbequina" olive orchards during pit hardening. Oil quality was determined by measuring analytical parameters for olive oil grading, antioxidant activity, total phenol content, fatty acid profile, volatile compounds profile, and sensory analysis. Oils from RDI were classified as "extra virgin olive oil" and their quality was improved due to their higher antioxidant potential (ABTS + [increased~75%] and DPPH˙[increased~25%] assays) and phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
5
8
1
Order By: Relevance
“…Arbequina oils extracted without leaves addition (control oils) are in line with the literature data, although with a slightly greater ripe fruity intensity compared to the scores reported for cv. Arbequina oils by Rodrigues et al [36] and Sánchez-Rodríguez et al [37]. Overall, the results also showed that the addition of olive leaves had a significant effect on the number and intensity of the perceived olfactory sensations (P value <0.05, one-way ANOVA).…”
Section: Impact Of Leaves Incorporation During the Extraction Of Oils On The Olfactory And Volatile Profilesmentioning
confidence: 71%
See 1 more Smart Citation
“…Arbequina oils extracted without leaves addition (control oils) are in line with the literature data, although with a slightly greater ripe fruity intensity compared to the scores reported for cv. Arbequina oils by Rodrigues et al [36] and Sánchez-Rodríguez et al [37]. Overall, the results also showed that the addition of olive leaves had a significant effect on the number and intensity of the perceived olfactory sensations (P value <0.05, one-way ANOVA).…”
Section: Impact Of Leaves Incorporation During the Extraction Of Oils On The Olfactory And Volatile Profilesmentioning
confidence: 71%
“…Arbequina oils [37,38]. On the other hand, it should be noticed that a wide range of contents has been reported for the same volatiles or chemical class, which could be attributed to the agroclimatic conditions, olive ripening index at harvest, and extraction methods used [3].…”
Section: Impact Of Leaves Incorporation During the Extraction Of Oils On The Olfactory And Volatile Profilesmentioning
confidence: 99%
“…86 Some studies reported that increasing amounts of water lead to a general increase of several VOCs, 67,78,85−88 while an opposite effect was reported by other researches. 86,87 These disagreements may be due to the influence of cv and environmental conditions on the effect of irrigation on the VOC profile. 51 Further studies are necessary to define deficit irrigation strategies that permit producers to standardize the product quality over the years no matter the seasonal climatic conditions, using the minimum water amount.…”
Section: Factors Influencing the Volatilementioning
confidence: 99%
“…As for the effect of plant water availability on VOO composition, it is well-known that water stress leads to higher phenolic contents in the obtained oils. , The effect on VOCs is instead not so well-defined: it has been reported that the water irrigation scheduling over the whole crop season affects the VOCs of VOOs of the Cornicabra cv more than the total content of water employed and that the effect of irrigation for Cobrançosa cv is more marked in drought than for rainy crops . Some studies reported that increasing amounts of water lead to a general increase of several VOCs, ,, while an opposite effect was reported by other researches. , These disagreements may be due to the influence of cv and environmental conditions on the effect of irrigation on the VOC profile . Further studies are necessary to define deficit irrigation strategies that permit producers to standardize the product quality over the years no matter the seasonal climatic conditions, using the minimum water amount.…”
Section: Factors Influencing the Volatile Composition Of Virgin Olive...mentioning
confidence: 99%
“…In contrast, although the cultivar is the main determinant of olive oil fatty acid composition, environmental factors and culture conditions have also been linked to variations in the fatty acid profile (Beltrán et al, 2004). Many studies have evaluated the effect of different water regimes on olive oil yield and composition (Fernández, 2014; Gonçalves et al, 2020; Sánchez‐Rodríguez et al, 2020), demonstrating that even if water stress decreases fruit yield (Greven et al, 2009; Moriana et al, 2003), fruit volume (Gómez‐del‐Campo et al, 2014), fresh weight, cell size (Rapoport et al, 2004) and the mesocarp/endocarp ratio (Gucci et al, 2009), olive oil content in the mesocarp is not affected (Costagli et al, 2003); however, the fatty acid composition can be slightly changed (Ahumada‐Orellana et al, 2018; Gómez‐Rico et al, 2007; Hernández et al, 2018; Tovar et al, 2002). In the processes of fruit growth and oil synthesis, photosynthesis and its limitation by water deficit play a key role since it is the main supplier of reduced carbon (Lawlor & Cornic, 2002).…”
Section: Introductionmentioning
confidence: 99%